2023
DOI: 10.3390/pharmaceutics15051433
|View full text |Cite
|
Sign up to set email alerts
|

Relating Molecular Dynamics Simulations to Functional Activity for Gly-Rich Membranolytic Helical Kiadin Peptides

Abstract: Kiadins are in silico designed peptides with a strong similarity to diPGLa-H, a tandem sequence of PGLa-H (KIAKVALKAL) and with single, double or quadruple glycine substitutions. They were found to show high variability in their activity and selectivity against Gram-negative and Gram-positive bacteria, as well as cytotoxicity against host cells, which are influenced by the number and placing of glycine residues along the sequence. The conformational flexibility introduced by these substitutions contributes dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…To verify the reliability of the model, we downloaded the latest discovered anticancer peptide sequences from the Frontiers in Genetics frontiersin.org DBAASP database (Pirtskhalava et al, 2021), Through biological experiments, it has been demonstrated that this sequence possesses functions such as anti-Gram+, anti-Gram-, and anticancer (Rončević et al, 2023). Moreover, this sequence is not included in our training dataset.…”
Section: Web Server Interface and Functional Confirmationmentioning
confidence: 99%
“…To verify the reliability of the model, we downloaded the latest discovered anticancer peptide sequences from the Frontiers in Genetics frontiersin.org DBAASP database (Pirtskhalava et al, 2021), Through biological experiments, it has been demonstrated that this sequence possesses functions such as anti-Gram+, anti-Gram-, and anticancer (Rončević et al, 2023). Moreover, this sequence is not included in our training dataset.…”
Section: Web Server Interface and Functional Confirmationmentioning
confidence: 99%